Exploring the Nexus between Young Marriage and Cervical Cancer Incidence - Sanjose, Lidya Nesya (Institute of Accounting Research and Novation (IARN), 2024)
Cervical cancer remains a significant global health challenge, disproportionately affecting women in low- and middle-income countries. While age at marriage has emerged as a potential risk factor for cervical cancer, the relationship between young marriage and disease incidence remains complex and poorly understood. This research study aimed to systematically investigate the association between young marriage and cervical cancer incidence, exploring mediating factors, temporal relationships, and disease progression pathways. Utilizing a retrospective cohort study design, data were collected from diverse populations of women of reproductive age, encompassing both urban and rural settings. Comprehensive demographic, clinical, and socio-economic information were retrieved from electronic health records, population registries, and national databases. Statistical analyses, including bivariate, multivariate, and longitudinal approaches, were employed to examine the association between age at marriage and cervical cancer risk, while controlling for potential confounders and mediating factors. The findings of the study revealed a significant association between young marriage and increased cervical cancer incidence, with women who married at younger ages exhibiting a higher risk of disease compared to those who married later in life. Socio-economic disparities, limited access to healthcare services, and risky sexual behaviors were identified as mediating factors influencing the relationship between age at marriage and cervical cancer risk. Longitudinal analyses indicated accelerated disease progression and earlier onset of cervical cancer among women who married at younger ages, highlighting the importance of early intervention and targeted screening programs for at-risk populations.